Clinical Cases in Autoimmune Blistering Diseases - Murrell, Dédée F.; Murrell, Dédée F. (Clinical Cases in Dermatology,, 2015)
This clinical case book serves as a useful guide for dermatologists, internists, family practitioners, pediatricians, and anyone else charged with the care of the skin. The case-based format distinguishes this work from a reference-style textbook, instead allowing readers to relate the presented cases to their own patients. Clinical Cases in Autoimmune Blistering Diseases provides help and insight for clinicians in managing this group of serious and debilitating skin conditions, with each case serving as a springboard for further pursuit and more extensive training. It will enable those new to the field to begin to develop a literacy and competence in autoimmune blistering diseases, while experienced dermatologists will find new ways to sharpen their diagnostic and treatment skills.